The Recurrent Landslides of Lagam Escarpment, Kaben Location, Marakwet East, Kenya - Loice, Kipkiror Jepkemboi; Rop, Kipsang Bernard; Namwiba, Wycliffe Habel (Machakos University Press, 2021)
The landslides of the Lagam escarpment in Kaben loction of Elgeyo Marakwet County are not only recurrent but are highly cataclysmic; causing mayhem whenever they occur. The first known landslides on the Lagam escarpment of Kaben location-Marakwet, happened during the 1961 El-Nino, when a major rainstorm hit the area (Kiptungu). These landslides re-fashioned Embosumer River and left huge boulders scattered over many farmlands. On the night of 12th April 2010, a catastrophic landslide hit Kaben location and again, Embosumer River was the perpetrator, having broken its banks due to excessive water inflow. Fourteen (14) people lost their lives, others got badly injured and lots of property was destroyed. Recently, on Sunday, 19th of April 2020, in the afternoon, heavy rains pounded the area causing massive mudslides that involved many rivers and streams. As a result, twenty-six (26) lives were lost, homes, schools and farmlands were washed away and to date, there are several bodies believed to be trapped in the mudslide material. This study is geared towards investigating the causes of the recurrent landslides and proposing possible mitigation measures. Data was collected through secondary data analysis and has been presented in the form of ground photographs, satellite images and discussions made thereon. It is hoped that this preliminary study of the Lagam escarpment landslides will create awareness pertaining to the recurrent landslides and draw positive action from the area residents and all concerned parties.
Keywords: Landslides; Recurrent; Lagam escarpment; Kaben Location; Marakwet